PENANGANAN ANAK KORBAN KEKERASAN - Nandang Mulyana; Risna Resnawaty; Gigin Ginanjar Kamil Basar (Institut Agama Islam Negeri Kendari, 2018)
This studi aims to analyze the treatment to child abuse at Kuningan regency, whether handling by government or nongovernment organisation. The causes of violence are categorized as internal factors that come from within the family and external that occur outside the family environment. The treatment for the the violence victims should be comprehensive and involving various competent parties. Thus, the involvement of all institutions, both government institutions and the public to handle the victims of violence is very important. Handling of the child victims of violence must also have a policy, which is not applied national but also more specific to each region. Parties involved in the treatment process of children victims include the Department of Social Affairs, Health Office, Education Office, Police, and P2TP2A. Meanwhile the community such as NGO need to concern on the victims of violence. This inter-institutional coordination is needed to support each other to overcome the children abuse and treat the victims. This is necessary because it is limited if only one institution which participate to overcome this issue.